Balancing Trade-off between Data Security and Energy Model for Wireless Sensor Network - Manjunath B. E.; P. V. Rao (Institute of Advanced Engineering and Science, 2018)
An extensive effort to evolve various routing protocol to ensure optimal data delivery in energy efficient way is beneficial only if there is additional means of security process is synchronized. However, the security process consideration introduces additional overhead thus a security mechanism is needed to accomplish an optimal trade-off that exists in-between security as well as resource utilization especially energy. The prime purpose of this paper is to develop a process of security in the context of wireless sensor networks (WSN) by introducing two types of sensor node deployed with different capabilities. The proposed algorithm Novel Model of Secure Paradigm (N-MSP) which is further integrated with WSN. However, this algorithm uses a Hash-based Message Authentication Code (HMAC) authentication followed by pairwise key establishment during data aggregation process in a WSN. The extensive simulation carried out in a numerical platform called MATLAB that depicts that the proposed N-MSP achieves optimal processing time along with energy efficient pairwise key establishment during data aggregation process